ANALISIS TINGKAT PERSEDIAAN OPTIMAL PRODUK FLEXI HOME PADA PT TELKOM INDONESIA KANDATEL MALUKU DIVISI TELKOM FLEXI - Harold - Hursepuny (Admisi dan Bisnis, 2013)
The objection of these research were : 1) to knew the length of customers demanding services on flexi home in 5 years ahead; also 2) to knew the length of optimal ordered quantity level, on the customer demanding in 5 years ahead.This research were a field research, which uses quantitative descriptive model, that been held from field research data as the primary data, on questionnaire and interview techniques also be supported by secondary data. Data analyzing used the Least Square projection method, to know the trend of demand customer; and Economic Order Quantity to know the trend of the economic order quantity.The results giving suggestion that the trend of demanding was arising, where on 2009 were 5.526 units; on 2010 were 5.533 units; on 2011 were 5.541 units; on 2012 were 5.548 units; and on 2013 were 5.556 units; and arising the EOQ at the level of 497 units on 2009; 498 units on 2010; on 2011 were 498 units; on 2012 were 498 units; and on 2013 were 499 units. Also the level of Reorder Point which: 45 units on 2009; on 2010 were 45 units; on 2011 were 46 units; on 2012 were 46 units and in 2013 were 46 units.